Intelligent traffic sign recognition system for autonomous vehicle navigation (ITSRS) - Law, Jia Swee (2018)
An autonomous vehicle generally provides certain level of recognition on obstacle detection, road detection and traffic sign recognition. There are existed system that can provide perfect assistance on the first two. However, traffic sign recognition is a field where people do not study much. Traffic signs play a key role on delivering important messages to the road users. Traffic Sign is designed by using different colors and shapes to attract the attention of road user. Sometimes, it brings confusion too. The algorithm studied in this paper has separated into two parts. First part will be carried out by using Microsoft Azure Custom Vision to train the traffic sign classifier. Then consume the model file in mobile application by using Android Studio.